Training Making Plastic Tempeh Hygienic (TEPIS) Post- Pandemic Era Covid 19 in Tanah Merah Residents - Sulistiyani Sulistiyani; Apsari Fajar Prihantini (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2022)
Purpose activity devotion this is coaching residents of Tanah Merah deep making Tempe Plastic Hygienic (EDGE) as effort Upgrade immune body and free from coronas. Partner in activity this is residents of Tanah Merah Bangkalan. activity this implemented with knowledge transfer method knowledge and technology with stages activity; 1) Planning, 2) implementation , and 3) evaluation . As for results from activity this is an effort to train and empower farmers in Tanah Merah-Bangkalan residents by increasing skills in processing food ingredients where it is hoped that Tegalwero Village farmers can master >75% the skills of making tempeh from soybeans packaged in hygienic plastic and continue the business of making tempeh from soybeans effectively independent, grow to be large so that the plan of this program will be a success. The food processing skills that are the main focus are the technique of making hygienic soybean tempeh by utilizing the potential of existing farmers' harvest of soybeans, Tanah Merah-Bangkalan residents to the fullest and making tempe products a special food of the city of salt. After a successful small-scale agro-industry program is developed, the economy of the Tanah Merah-Bangkalan people will automatically change from a traditional agricultural system to an entrepreneurial-based economy. So that the community can also become entrepreneurs, coupled with the fact that the presence of tempeh consumed by humans will reduce the number of corona viruses that attack humans.